Health–related quality of life and related factors among members of family medicine teams at Kerman University of Medical Sciences, Iran - Khalooei, Ali; Homaei, Zahra (Social Determinants of Health, 2017)
Background: Different factors affect the health care workers’ health and quality of life which lead to reduced performance, quality, and safety of services provided. The present study aimed to evaluate health-related quality of life (HRQoL) and its related factors among members of family medicine teams (FMTs). Methods: A cross-sectional descriptive study was carried out in the winter of 2015. Using SF36 questionnaire, HRQoL of all FMTs (physicians, midwives, and health technicians) at Kerman University of Medical Sciences was evaluated. Data were analyzed using Independent T test, ANOVA, Pearson Correlation coefficient, and multiple linear regression in IBM SPSS Statistics for Windows, Version 22.0. Results: Mean (SD) of total HRQoL score in FMTs was 71.6 (12.3) (out of 100). The Means (SD) of Physical Component Summary (PCS) and Mental Component Summary (MCS) scores were 75.1(14.3) and 68.0 (14.2), respectively. Also, there was a positive correlation (r=0.49) between the PCS and MCS (P<0.001). Multivariate linear regression analysis showed that work experience was a predictor for total HRQoL (P<0.001) and PCS (P<0.001), while marital status was a predictor variable for MCS (P=0.04). Conclusion: The results of the current study revealed that HRQoL, particularly the MCS, is not at an appropriate level among FMTs. Therefore, it is necessary to design and implement interventions in order to increase their quality of life, especially with focus on mental aspect.